2012
DOI: 10.1183/09031936.00175611
|View full text |Cite
|
Sign up to set email alerts
|

Massive monoclonal expansion of CD4 T-cells specific for aMycobacterium tuberculosisESAT-6 peptide

Abstract: T-cell responses towards tuberculin (purified protein derivative; PPD) or the Mycobacterium tuberculosis-specific antigens early secretory antigenic target (ESAT)-6 and culture filtrate protein-10 are indicative of prior contact with mycobacterial antigens. In this study, we investigated the exceptional case of a 75-yr-old patient who devoted more than one-third of his CD4 T-cells against PPD and ESAT-6.Antigen-specific T-cells were characterised using flow cytometric intracellular cytokine staining, ELISPOT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Because previous studies of the effect of latent or active TB on immune activation have primarily characterized HIV-uninfected individuals, and because we were specifically interested in immune activation markers implicated in HIV pathogenesis, we only assessed these markers in HIV co-infected subjects. While previous studies have found no evidence for elevated immune activation (of either bulk T-cells or M. tb -specific T-cells) in latently-infected, HIV-negative individuals ( Rodrigues et al, 2002 , Wergeland et al, 2011 , De Almeida et al, 2012 , Adekambi et al, 2012 , Hodapp et al, 2012 ), our data suggest that this is not the case for HIV-infected individuals who also harbor latent TB infection. This surprising finding challenges the notion of latency as a fully dormant state of TB infection, and suggests that HIV co-infection may skew this heterogeneous state towards a state that immunologically resembles more active infection.…”
Section: Discussioncontrasting
confidence: 99%
“…Because previous studies of the effect of latent or active TB on immune activation have primarily characterized HIV-uninfected individuals, and because we were specifically interested in immune activation markers implicated in HIV pathogenesis, we only assessed these markers in HIV co-infected subjects. While previous studies have found no evidence for elevated immune activation (of either bulk T-cells or M. tb -specific T-cells) in latently-infected, HIV-negative individuals ( Rodrigues et al, 2002 , Wergeland et al, 2011 , De Almeida et al, 2012 , Adekambi et al, 2012 , Hodapp et al, 2012 ), our data suggest that this is not the case for HIV-infected individuals who also harbor latent TB infection. This surprising finding challenges the notion of latency as a fully dormant state of TB infection, and suggests that HIV co-infection may skew this heterogeneous state towards a state that immunologically resembles more active infection.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been reported that CD4 + T cell-mediated immunity plays a critical role in controlling chronic bacterial and viral infections [10,21-24]. In the present study, we showed that the use of our gene melting spectral pattern (GMSP) assay to study TCRBV gene families in PBMCs, CD4 + and CD8 + T cell subsets from subjects with active TB or LTBI was helpful in the differential diagnosis and treatment of active TB or LTBI.…”
Section: Discussionmentioning
confidence: 53%
“…It has yielded encouraging results when used to detect humans infected with M. Tuberculosis [16][17][18][19][20][21][22][23]. One major advantage of CFC is that it provides an opportunity to count the number of responding cells and simultaneously determine their Table 1 Receiver operator characteristics (ROC) analyses of antigen-specific IFN-␥ producing CD4 + T cells frequencies to distinguish between infection states.…”
Section: Discussionmentioning
confidence: 98%